Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/advs.201902767
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of All‐Inorganic Perovskite Single Crystal Arrays on Electron Transport Layer

Abstract: Directly growing perovskite single crystals on charge carrier transport layers will unravel a promising route for the development of emerging optoelectronic devices. Herein, in situ growth of high‐quality all‐inorganic perovskite (CsPbBr3) single crystal arrays (PeSCAs) on cubic zinc oxide (c‐ZnO) is reported, which is used as an inorganic electron transport layer in optoelectronic devices, via a facile spin‐coating method. The PeSCAs consist of rectangular thin microplatelets of 6–10 µm in length and 2–3 µm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
(103 reference statements)
2
16
0
Order By: Relevance
“…In addition to heteroepitaxial growth in the vapor phase, solution-phase heteroepitaxial growth has emerged to enable the epitaxy of halide perovskite nanostructures on a substrate. SrTiO 3 (100) and cubic zinc oxide (c-ZnO) have been used as substrates for the growth of CsPbBr 3 single-crystalline NPs by spin-coating. , For instance, c-ZnO enables the epitaxial growth of cubic-phase CsPbBr 3 via the epitaxial lattice match (100) CsPbBr 3 ∥(100) c-ZnO . The authors argued that the crystal facet mismatch of 19% (lattice constants: 5.605 Å for (100) CsPbBr 3 and 4.6 Å for (100) c-ZnO) allows for the solution-phase epitaxial growth of CsPbBr 3 on c-ZnO.…”
Section: Halide Perovskite Nanoplates and Arraysmentioning
confidence: 99%
“…In addition to heteroepitaxial growth in the vapor phase, solution-phase heteroepitaxial growth has emerged to enable the epitaxy of halide perovskite nanostructures on a substrate. SrTiO 3 (100) and cubic zinc oxide (c-ZnO) have been used as substrates for the growth of CsPbBr 3 single-crystalline NPs by spin-coating. , For instance, c-ZnO enables the epitaxial growth of cubic-phase CsPbBr 3 via the epitaxial lattice match (100) CsPbBr 3 ∥(100) c-ZnO . The authors argued that the crystal facet mismatch of 19% (lattice constants: 5.605 Å for (100) CsPbBr 3 and 4.6 Å for (100) c-ZnO) allows for the solution-phase epitaxial growth of CsPbBr 3 on c-ZnO.…”
Section: Halide Perovskite Nanoplates and Arraysmentioning
confidence: 99%
“…Impurity element detection is one of these applications, which is not applicable using nanoparticles. Apart from impurity detection, energy storage, 117 gas and chemical sensing, 118 optoelectronics, 20,119 anti-bacterial, 120 cancer treatment, 121,122 cellular imaging, 123,124 electronics, 125 and photocatalytic activity 126 are the other major application elds of QDs. However, these QDs will denitely augment the performance of these devices, which have based on nanoparticles to date.…”
Section: Applicationmentioning
confidence: 99%
“…It has been reported that the large lattice mismatch of the perovskite layer and an underlayer (e.g.t ransparent substrates,m etal oxide) significantly affects the strain that will push the perovskite phase out of the state of thermodynamic equilibrium. [84] Wang et al [85] reported that deposited cubic ZnO (c-ZnO) enables the formation of phase-pure cubic CsPbBr 3 perovskite single-crystal arrays (PeSCAs) because of an epitaxial lattice coherence between CsPbBr 3 and c-ZnO. ThePeSCAs demonstrate amuch superior structural stability in ambient environment over the perovskite nanocrystals, along with al ower density of trap states and longer carrier lifetimes.However,itisdifficult for hexagonal crystal phases of ZnO to induce the formation of cubic CsPbBr 3 due to the large lattice mismatch (Figure 8).…”
Section: Hysteresismentioning
confidence: 99%